The Factors Affecting Project Implementation Activities in State Corporation: A Case of National Oil of Kenya (NOCK) - Malasi, Sebastian; Kagiri, Dr. Asumptah (International Journal of Entrepreneurship and Project Management, 2016)
Purpose: The purpose of this study is to examine the factors affecting project leadership activities in State Corporation, a case of National Oil Corporation of Kenya (NOCK). Specifically, to analyze the effect of political insurgency, the effect of interest rate and the effect of agency control on project implementation in NOCK. Methodology: Descriptive design was used in order to describe the factors affecting project leadership activities in NOCK. The population targeted for this study was 426 employees of NOCK Nairobi industrial area. Stratified random sampling was used. The researcher picked a sample size of 63 employees. The study used both secondary and primary data collection methods. The researcher pre-tested the questionnaires to ensure reliability and validity of data collected. Data was analyzed quantitatively by describing or summarizing data using descriptive statistics. Qualitative data from in-depth interview was also analyzed. Results: The study discovered that most projects at NOCK are not implemented well and there is problem on political insurgency, interest rate and agency control. The study established that political insurgency affects the project implementation activities due to government control of the corporation. Further, the study revealed NOCK liaises with the Central Bank of Kenya on monetary and fiscal issues but the task team does not implement the findings. Unique contribution to theory, practice and policy: In light of the study findings, NOCK should have a qualified and professional project management manager to spearhead project implementation activities. The Board of Directors of NOCK should fully support project implementation activities by allocating enough funds to the project team and ensure that the decisions are adhered to.